An unusual lupus like malar rash pattern with hepatosplenomegaly as a presentation of gamma delta t cell lymphoma: An unusual lupus like malar rash pattern with hepatosplenomegaly as a presentation of gamma delta t cell lymphoma - Bani-Mustafa, Ala’a Abdullah Hussein; Yousef Mustafa Magableh, Ahmad; bawa'neh, Hisham Subhi Hussin; alrosan, Zaid Nu’man Abdel Latif (International Journal of Scientific Research and Management (IJSRM), 2023)
About 12% of all lymphoid tumors worldwide are peripheral t cell lymphomas, which are uncommon subtypes of non-hodgkin lymphoma. they have a poor prognosis and are more common in populations and countries in asia. T cell lymphomas with gamma delta t cell receptors expressed in them are very rare (less than 1% of lymphoid neoplasms) and extremely aggressive; they originate from gamma delta t cells; a small subset of peripheral t cells with direct antigen recognition capability acting at the interface between innate and adaptive immunity .Lymphoid tissue, skin, gastrointestinal tract, and the red pulp of the spleen are where gamma delta t lymphocytes tend to cocentrate, representing only 1-5% of the total circulating lymphocytes, but accounting for up to 30% of the entire t cell population.In contrast to alpha beta t cells, gamma delta t lymphocytes develop from cd4/cd8 thymic precursors in the bone marrow and usually lack the major histocompatibility complex restriction.These lymphocytes conduct as cytotoxic cells similar to natural killer cells in their activity as early effectors of innate, non-specific immune response and are capable of t cell receptor rearrangement as well as phagocytosis.Hepatosplenic t cell lymphoma and primary cutanous gamma delta cell lymphoma are recognized as two different gamma delta t cell lymphoma entities.A well characterized extranodal lymphoma, hepatosplenic t cell lymphoma has a disguised onset, secondary to intrasinusoidal infiltrationn of the spleen, liver, and bone marrow, has a rapidly progressive course, is poorly responsive to chemotherapy.A panniculitis-like clinical picture with prominent epidermal involvement can be a presentation of primary cutaneous gamma delta t cell lymphoma. In this case study , the authors will discuss a case of 19 year old male patient present with a lupus like malar rash and hepatosplenomegaly  and who had been diagnosed with gamma delta t cell lymphoma.